Trauma Emosional Remaja Keluarga dengan Kekerasan dan Perselingkuhan: Studi Fenomenologis - Nazarlin, Nazarlin; Martin, Sri Novia; Damra, Hanny Rufaidah; Irta, Aflah Zakinov (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Adolescents growing up in families experiencing violence and infidelity face complex emotional challenges. An unsafe family environment can create traumatic experiences that influence social behavior, such as tendencies to withdraw, fear of interaction, and difficulties in building interpersonal relationships. This research aims to explore more deeply the emotional trauma experienced by adolescents living in families with violence and infidelity. The study uses a qualitative approach with a phenomenological method, and the data is analyzed using Interpretative Phenomenological Analysis (IPA) techniques. The participant is a university student in the late stage of adolescence living in the city of Padang. Data was collected through semi-structured interviews. The research findings reveal three main themes: (1) experiences of emotional violence from the father, (2) the impact of infidelity in the family on the adolescent’s psychological condition, and (3) the adolescent’s efforts to build resilience amid emotional pressure. This study emphasizes that emotional trauma resulting from harsh parenting and experiences of betrayal within the family can significantly affect the social and emotional development of adolescents.